Strength and failure analysis of inverse Z joints bonded with Vinylester Atlac 580 and Flexo Tix adhesives - Adin, Hamit; Turgut, Aydin (Korean Soc Mechanical Engineers, 2012)
In this study, the tensile strength and failure loads of the inverse Z joints were analyzed both experimentally and numerically by using two adhesives with different properties under a tensile load. Vinylester Atlac 580 and Flexo Tix were used as adhesives and the joints were prepared with two different composite materials. Initially, the mechanical properties of the adhesives were specified using bulk specimens. Then, the stress analyses were performed using three-dimensional finite element method (3-D FEM) via Ansys (V.10.0.1). The experimental results were compared with the numerical results and they were found quite reasonable. According to the test results, it can be seen that when the adherend thickness is increased, the stress increases as well. The most appropriate value of the adherend thickness is identified as t = 5 mm. Furthermore, it was observed that the lowest failure load was obtained at t = 3 mm the thickness for each specimen.
Keywords: Adhesive; Composite material; Stress analysis; Ansys; Finite element method (FEM)